Expand using formula (7-3y) square.
solve
step by step answer
Answers
Answered by
1
╒═════════════════════╕
☬ YOUR ANSWER ☬
╘═════════════════════╛
⇣⇣⇣⇣⇣⇣⇣⇣⇣⇣⇣⇣⇣⇣⇣⇣⇣⇣⇣⇣⇣⇣⇣⇣⇣⇣⇣⇣⇣⇣⇣⇣⇣
As we know,
⏩Using identity,
⏩(a - b )² = a² + b² - 2(ab)
⏩(7 - 3y)² = 7² + (3y)² - 2 (7)(3y)
⏩=49 + 9y² - 42y
⇡⇡⇡⇡⇡⇡⇡⇡⇡⇡⇡⇡⇡⇡⇡⇡⇡⇡⇡⇡⇡⇡⇡⇡⇡⇡⇡⇡⇡⇡⇡⇡
╒══════════════════════╕
☬ THANKS! @Brainlyconquerer ☬
╘══════════════════════╛
☬ YOUR ANSWER ☬
╘═════════════════════╛
⇣⇣⇣⇣⇣⇣⇣⇣⇣⇣⇣⇣⇣⇣⇣⇣⇣⇣⇣⇣⇣⇣⇣⇣⇣⇣⇣⇣⇣⇣⇣⇣⇣
As we know,
⏩Using identity,
⏩(a - b )² = a² + b² - 2(ab)
⏩(7 - 3y)² = 7² + (3y)² - 2 (7)(3y)
⏩=49 + 9y² - 42y
⇡⇡⇡⇡⇡⇡⇡⇡⇡⇡⇡⇡⇡⇡⇡⇡⇡⇡⇡⇡⇡⇡⇡⇡⇡⇡⇡⇡⇡⇡⇡⇡
╒══════════════════════╕
☬ THANKS! @Brainlyconquerer ☬
╘══════════════════════╛
Answered by
0
3y squ are - 7 = cube root 3y
Similar questions
Biology,
7 months ago
Social Sciences,
7 months ago
Math,
7 months ago
Math,
1 year ago
CBSE BOARD X,
1 year ago
Math,
1 year ago
World Languages,
1 year ago